Effect of chronic administration of cisapride on gastric emptying of a solid meal and on dyspeptic symptoms in patients with idiopathic gastroparesis. Issue 3 (March 1987) - Corinaldesi, R; Stanghellini, V; Raiti, C; Rea, E; Salgemini, R; Barbara, L
Abstract : In a double blind crossover comparison with placebo, the effects of cisapride (10 mg tid for two weeks), a non-antidopaminergic gastrointestinal prokinetic drug, on gastric emptying times and on symptoms were evaluated in 12 patients with chronic idiopathic dyspepsia and gastroparesis. Gastric emptying was studied by a radioisotopic gamma camera technique. The test meal was labelled in the solid component (99mTc-sulphur colloid infiltrated chicken liver). Nine symptoms (nausea, belching, regurgitations, vomiting, postprandial drowsiness, early satiety, epigastric pain or burning, heartburn) were graded weekly on a questionnaire. Cisapride was significantly more effective than placebo in shortening the t1/2 of gastric emptying (p2 = 0.04), but no significant difference was observed between the two treatments with regard to the improvement of total symptom score (p2 = 0.09). No side effects were reported during the study.